Evidence for Conical Magnetic Structure in M‐Type BaFe12O19 Hexaferrite: A Combined Single‐Crystal X‐ray Magnetic Circular Dichroism and Neutron Diffraction Study. Issue 6 (8th March 2021) - Kumar, Keshav; Mishra, Shrawan Kumar; Singh, Sanjay; Baev, Ivan; Martins, Michael; Orlandi, Fabio; Manuel, Pascal; Pandey, Dhananjai
Abstract : The magnetic ground state of BaFe12 O19 (BFO) is investigated using X‐ray absorption spectra (XAS), X‐ray magnetic circular dichroism (XMCD), and neutron diffraction studies at 1.2 and 1.5 K, respectively. The XMCD measurements on single‐crystals of BFO in grazing‐incidence geometry reveal canting of the spins away from the c ‐axis of the hexagonal unit cell. Single‐crystal neutron diffraction studies reveal magnetic satellite peaks along the 00l reciprocal lattice row around the forbidden l = 2 n ± 1 positions confirming the conical‐type magnetic structure in the ground state of BFO. The observation of the conical magnetic structure of BFO opens the possibility of type‐II multiferroicity in undoped BFO. Abstract : Results of XMCD and neutron diffraction studies on BaFe12 O19 single crystals are presented, which reveal departure from the Gorter‐type collinear magnetic structure. The magnetic ground state of BaFe12O19 is shown to correspond to a longitudinal conical incommensurate modulation of the collinear magnetic structure, as confirmed by the observation of characteristic magnetic satellite peaks.